Reliability Impact Of Demand Side Menagement (DSM) In A Wind Integrated Power System - Yusuf, Sabar (Universiti Sains Malaysia, 2017)
Wind energy conversion system (WECS) are becoming popular because of their economical values compared to conventional sources. The biggest problem face by WECS is the inconsistent availability of wind potential and this will affect the overall power system reliability. Demand side management (DSM) is one of the potential method in meeting this problem by improving the overall system reliability by load shifting. The objectives of this thesis are to study the reliability impact of DSM in a wind integrated power system, modify IEEE Reliability Test System (IEEE-RTS) by incorporating WECS and DSM as a test system and simulate the real behaviour patterns of a wind integrated power system by using Monte Carlo simulation (MCS). The load models for all busses and generation capacity at each hour in a year of the modified IEEE-RTS is stimulated and the system Expected Energy Not Served (EENS) is computed as a reliability index. From this project, it is known that DSM load shifting technique give a significant improvement in the system overall reliability especially load shifting at 80%. Applying load shifting to each individual bus yield slightly better improvement in system reliability compared to applying it to the system total load. Load shifting also shows positive improvement to system reliability for various Wind Turbine Generator (WTG) power capacity.